Evolving standards of care in the age of cybertechnology. (16th April 2018) - Reamer, Frederic G.
Abstract : Behavioral health professionals are making increased use of cybertechnology to deliver services to patients, communicate with patients, gather information about patients, and communicate with colleagues. The advent of cybertechnology – included the Internet, text (SMS), email, video, cloud storage of electronic records, and other forms of electronic communication and documentation – has introduced novel and unprecedented ethical and risk‐management challenges. This article provides an overview of emerging issues related to informed consent; delivery of services; privacy, confidentiality, and privileged communication; boundary issues and dual relationships; documentation; and practitioners' relationships with colleagues. The author highlights new standards of care that are being incorporated into licensing statutes and regulations; professional codes of ethics; and practice guidelines adopted by the professions of psychiatry, psychology, mental health counseling, marriage and family therapy, and clinical social work.